Intranasal insulin for treatment of delirium in older hospitalised patients: study protocol for a randomised controlled trial - Meera Agar; Barbara Toson; Jacqueline Close; Andrew Milne; Gideon Caplan; Anita Nitchingham; Bernard Tuch (BMJ Open)
Introduction Delirium is one of the most common conditions diagnosed in hospitalised older people and is associated with numerous adverse outcomes, yet there are no proven pharmacological treatments. Recent research has identified cerebral glucose hypometabolism as a pathophysiological mechanism offering a therapeutic target in delirium. Insulin, delivered via the intranasal route, acts directly on the central nervous system and has been shown to enhance cerebral metabolism and improve cognition in patients with mild cognitive impairment and dementia. This trial will determine whether intranasal insulin can reduce the duration of delirium in older hospitalised patients.Methods and analysis This is a prospective randomised, placebo-controlled, double-blind study with 6 months follow-up. One hundred patients aged 65 years or older presenting to hospital with delirium admitted under geriatric medicine will be recruited. Participants will be randomised to intranasal insulin detemir or placebo administered twice daily until delirium resolves, defined as Confusion Assessment Method (CAM) negative for 2 days, or discharge from hospital. The primary outcome measure will be duration of delirium using the CAM. Secondary outcome measures will include length of hospital stay, severity of delirium, adherence to treatment, hospital complications, new admission to nursing home, mortality, use of antipsychotic medications during hospital stay and cognitive and physical function at 6 months postdischarge.Ethics and dissemination This trial has been approved by the South Eastern Sydney Human Research and Ethics Committee. Dissemination plans include submission to a peer-reviewed journal for publication and presentation at scientific conferences.Trial registration number ACTRN12618000318280.